Los jóvenes y su relación con la política, descripción de las representaciones sociales sobre la política en jóvenes - Cruz Suárez, Luis Carlos (Universidad Antonio Nariño, 2021)
The present work aims to study the social representations in young university students, in summary, the main objective is to describe the social representations that young psychology students from the Antonio Nariño University have about politics. To achieve this objective, the concepts of social representation, the concept of politics, that of youth and the concept of political subjectivity were adopted as theoretical support.